Pengaruh Kualitas Layanan, Kepercayaan, Dan Citra Perusahaan Terhadap Kepuasan Nasabah (Studi Pada Nasabah PT. Bank BPR UMKM JATIM Cabang Mojokerto) - Laidia Himmatul Ulya; Siti Asiyah; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine and analyze the effect of service quality, trust and corporate image on customer satisfaction. The population in this study were customers of PT. Bank BPR UMKM East Java Mojokerto Branch that uses products/services at PT. Bank BPR UMKM East Java Mojokerto Branch with a total sample of 100 respondents. The analysis method uses multiple linear regression analysis. Sampling technique with non probability sampling technique with purposive sampling method. The results showed that the variables of service quality, trust and corporate image simultaneously affect customer satisfaction. The variables of service quality, trust and company image partially have a positive and significant effect on customer satisfaction. Keywords: Service Quality, Trust, Company Image, Customer Satisfaction.